Descriptive Study the Characteristics Of Mothers With Postpartum Depression Screening Results On The Seventh Day Puerperium - Khoyin Irma Diana; Rita Yulifah; Ita Yuliani; Didien Ika Setyarini (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Postpartum depression is a psychological disorder that occurs during the postpartum period. The incidence of postpartum depression in Indonesia is between 50-70%. The development of the baby and the mother’s social life can be severely affected by postpartum depression. Screening is necessary to anticipate the incidence of postpartum depression. The purpose of this study was to describe the characteristics of mothers with postpartum depression screening results on the seventh day of postpartum women. The design of this study was a quantitative descriptive with a cross-sectional approach. The population of 38 people used the total sampling technique so that the total sample was 38 people. The research instrument used a general data questionnaire and EPDS. The results of the study showed that postpartum mothers who experienced a risk of postpartum depression were 21.1%. Based on the characteristics, namely mothers aged 20-35 years (18.4%), primiparous (13.2%), spacing of children <2 years (8.7%), mothers who do not work (15.8%), and mothers with senior high school education (15.8%). The risk of depression experienced by postpartum mothers in Blimbing, Malang is thought to be caused by factors such as parity, distance between children and education level. Although in small numbers. Postpartum depression can have a negative impact on the mental health of the mother and the development of the child in the future, so depression screening needs to be tried so that the coverage of early detection of postpartum depression increases.